(untitled) (International Journal of Food and Nutritional Sciences, 2021)
In this project, we propose a robot named Medi-Robot with some functionality of providing medicine as well as to measure the vital parameters (Heart rate and Temperature) of the patient. During the current scenario, reducing the human to human contact in hospitals is required. In a bid to prevent doctors and medical staff from getting affected by Corona virus the role of medicine delivering robots are evolving. We can attain the locomotion procedure of the robot using the principle of Radio-frequency identification (RFID) that automatically identifies and tracks tags attached to the objects. The movement and finding the path to patient location is done through with Bluetooth module to navigate the robot and with RFID tag. To navigate the robot by the help of Bluetooth module and give the commands from the mobile like forward, backward, left, right, stop commands. The robot will move towards the patient’s room by following user commands and use RFID cards to identify the patient’s room number. Using the vending machine the medicine delivery is made possible to the patients. All the measured parameters will be stored to the cloud using the application of the Internet of Things (IoT). All the data will successfully be sent to the cloud through the Node MCU.